Traceability issues in the trade of marine ornamental species - Cohen, Felipe P. A. (2018)
In the last decade, the trade of marine ornamental species has experienced a significant expansion worldwide; however, this industry still relies on a large number of unsustainable practices (e.g., cyanide fishing, overexploitation of target species) and needs to shift its operations urgently to avoid collapsing. Under this scenario, traceability and certification emerge as important management tools that may help this industry to shift toward sustainability. This industry relies on the trade of thousands of small-sized species that are traded live on a unitary basis with high market value. These features, along with a fragmented and complex supply chain, make the traceability of marine ornamental species a challenging task. This study presents the most commonly used methods to trace aquatic organisms and discusses their suitability to trace marine ornamental species. The use of bacterial fingerprints appears to be the most promising method to successfully trace marine ornamentals, but it is most likely that a combination of two or more traceability methods need to be implemented to cover all the unique features displayed by the live trade of marine ornamental species.